PENEGAKAN HUKUM TENTANG TINDAK PIDANA NARKOTIKA YANG MELIBATKAN ANAK DIBAWAH UMUR SEBAGAI KURIR DI WILAYAH DEPOK - Zulfikar Aji Kurniawan (2021)
Drug abuse among children is a crime that violates the law. The rise of drug or drug abuse perpetrators can affect the mental and educational of children as the next generation of the nation.This study aims to find out the preventive measures of law enforcement against perpetrators who cause children to be involved in drug use crimes as well as efforts made by law enforcement in tackling drug abuse involving children.